Afferent Neural Branching at Human Acupuncture Points: Do Needles Stimulate or Inhibit? - Silberstein, Morry; Adcroft, K.; Wan, A.; Massi, Massimiliano (Mary Ann Liebert, Inc., 2012)
Background: Acupuncture has previously been considered to be stimulatory to the nervous system; however, the specific mechanism for this remains unknown, with the few published studies of acupuncture-point histology showing reduced numbers of nerves and neural receptors at acupuncture-point sites. Objective: This study was undertaken to visualize the neuroanatomic features of acupuncture points in humans. Materials and Methods: Light microscopy was performed on silver-stained sections of a human cadaver at P 6, and confocal microscopy was performed on PgP9.5 and P2X3 immunostained sections of 2 points (GB 20 and SP 6) from a live human volunteer. Results: At each point, but not at control sites, a single nerve bundle extending to the dermal–epidermal junction was identified where it branched into two parts, with each branch running perpendicularly, parallel to the dermal–epidermal junction. Conclusions: Acupuncture may incise afferent unmyelinated axonal branch points, disrupting both neural transmission to the spinal cord and crosstalk along meridians, while simultaneously stimulating larger, myelinated afferents, thus explaining both the immediate and long-lasting effects of acupuncture.